Development of strain-based fatigue life calculation software for variable amplitude loading data - Mohd Radzi, Abd Rashid (2010)
This thesis presents the development of strain-based fatigue life calculation software for variable amplitude loading data. The main objective of this study is to develop calculation software for fatigue life prediction using MATLAB®. The software allows life predictions to quickly provide fatigue crack initiation using SAESUS data and road loading history on car lower suspension arm. In addition, the fatigue life was predicted using strain life approach subjected to variable amplitude loading. Coffin Manson are the method that provides in the software. Rainflow cycle counting method will be use to extract the cycle from time series data. Then the Palmgren-Rules equation was utilized to calculate cumulative damage. As a result, the GUI will display the result from the method using. From the software development, it can contribute to all user for calculate life prediction especially for variable amplitude loading. Thus the software does not need higher cost and also user friendly.